Clinical and electrophysiological features of peripheral neuropathy in older patients with lung carcinoma - Tomanović Vujadinović, Sanja; Jovanović, Dragana; V. Ilić, Nela; Dubljanin-Raspopović, Emilija; Nedeljković , Una; Ilić, Branka; Samardžić, Natalija; Ćeriman, Vesna; Stević, Zorica; Marković Denić, Ljiljana (Vojnosanitetski pregled, 2021)
Background/Aim. Peripheral nervous system affection in people with lung cancer is commonly associated with paraneoplastic neuropathy. However, clinical studies evaluating the frequency, clinical, and electrophysiological characteristics of peripheral neuropathies which are not related to onconeuronal antibodies, in this, on average, older population of patients, are very rare. The aim of this study was to define the frequency, as well as clinical and electrophysiological characteristics of idiopathic neuropathies in patients suffering from lung cancer in early stages of the diseases. Methods. Clinical and electrophysiological data of 105 elderly subjects (age 63.4 ± 7.8 years) suffering from lung carcinoma who underwent extensive neurological and electrophysiological evaluation (nerve conduction studies) between 2013–2018 were estimated. Exclusion criteria were “classical” paraneoplastic neurological syndromes with onconeuronal antibodies present, as well as patients with typical known causes of peripheral neuropathy (e.g. diabetes, alcoholism, chronic renal insufficiency, vitamin deficiencies, etc.). Results. There were 19.1% patients with clinically manifest neuropathies, with additional 37.1% patients with only electrophysiological abnormalities. The most frequent pathophysiological pattern was axonal pathology (71.2%) with predominantly distal and symmetrical distribution (86.4%). Conclusion. Patients with lung cancer in the early stages of the disease show a high incidence of clinically minor damage of the nerves, according to the pattern of chronic sensomotor distal neuropathy, with predominance of axonal damage. These findings underline the importance of a detailed clinical and electrophysiological evaluation in this category of patients who are without the typical etiological factors for peripheral neuropathies since, during cancer therapy, patients undergo a series of treatments with additional risk for the development/aggravation of neuropathy.
Keywords: lung neoplasms; polyneuropathies; comorbidity; aged; electrophysiology